Rapid differentiation of mafic to intermediate magma constrained by Ra–Th disequilibrium and the size of magma chamber beneath Hekla volcano, Iceland - Sigmarsson, Olgeir; Larsen, Guðrún; Hervé, Garance (Contributions to Mineralogy and Petrology, 2024)
co auteur étranger International audience The size of deep-seated magma chambers is an important parameter for understanding pre-eruptive signals such as surface deformation. The constantly inflating Hekla volcano in Iceland has had relatively simple eruptive behaviour during the historical period. The eruptions start explosively with production of differentially evolved andesite magma to dacite, related to the length of the foregoing quiescence period, and ends with an emission of a basaltic andesite lava of uniform composition. The basaltic andesite is formed by fractional crystallisation from a deeper-seated basalt source in a steady-state manner. How fast such a differentiation mechanism operates is unknown. Measured Ra–Th radioactive disequilibrium in both the basalt and the basaltic andesite reveal a decrease from a 14% excess of 226 Ra over 230 Th to only 5% with magma differentiation. The decrease in 226 Ra excess to 5% in the basaltic andesite of Hekla is shown to be controlled by plagioclase fractionation alone. Therefore, the magma differentiation time from basalt to intermediate magma beneath Mt. Hekla is significantly shorter than three centuries, the time needed to detect significant 226 Ra-decay. Given the steady-state production of basaltic andesite magma and the estimated magma production rate, the volume of the basaltic andesite magma reservoir can be estimated as less than 2 km 3.